The Medium, the Mystic, and the Physicist: Toward a General Theory of the Paranormal by Lawrence LeShan - Bova, Michael (Journal of Scientific Exploration, 2013)
The Medium, the Mystic, and the Physicist, first published in 1974, reads as if it were published this week. The premise of this classic remains relevant to contemporary parapsychologists and to those of other disciplines taking part in the study of consciousness. LeShan describes his book as, "a story of adventure, as a search for the meaning of impossible events," giving examples of anomalous perceptions from laboratory experiments, spontaneous cases, mediumistic cases, and from the psychotherapy setting which beg for a theory to explain them. This book describes his theory of the paranormal and the adventure of shaping this theory. LeShan interviewed serious sensitives who had a high frequency of paranormal events in their lives. During the years of LeShan's inquiry, it became clear that at the moment when paranormal information was acquired (when "telepathy" or "clairvoyance" or "precognition" was happening), sensitives were reacting to the world as if it were constructed and "worked" differently than what we normally believe it to be. At those moments they used a different metaphysical structure of the world than our ordinary, everyday, metaphysical structure. LeShan identified two other groups, mystics and Einsteinian physicists, who reached the identical conclusion: that there are two ways of being in the world, which LeShan calls the Sensory Reality for our usual way of knowing, and the Clairvoyant Reality, independently described by these groups where information is gained other than through the senses, with a unity of subject and object and an experiential quality of deep wholeness. We get a chance to see this, almost intimately, by reading Eileen Garrett's sessions with LeShan and in quotes from other sensitives, mystics, and physicists, bringing the Clairvoyant Reality within our grasp.